Contemporary Art from Poland. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1986)
Baldyga, Janusz ; Bernacki, Piotr ; Brogowski, Leszke ; Dudek, Andrzej ; Dwurnik, Edward ; Dzieamski, Grzegorz ; Gierzynska, Teresa ; Jez, Zbigniew ; Kazmierczak, Wladyslaw ; Konart, Tomasz ; Konart, Iwona ; Kolodrubiec, Janusz ; Kostolowski, Andrzej ; etc.
Contemporary Art from Poland, Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff, July 5 -28, 1985
boek